RESSOCIALIZAÇÃO E RECONSTRUÇÃO DA IDENTIDADE, O DESAFIO DO SISTEMA CARCERÁRIO BRASILEIRO: UM ESTUDO DE CASO - Freire, Phablo; Yanne da Silva Simões, Rerika (LINKSCIENCEPLACE, 2026)
This study aims to identify if the perception of subjects on the resocialization process, inmates and prison guards, in direct contact with the phenomenon. Regarding the method research it is located in the legal and sociological theoretical and methodological aspects of the legal type diagnosis. The techniques and procedures for data collection semi-structured questionnaires were used to arrest the perceptions and demographic data partner. The thematic content analysis of Bardin was used to identify the representations of the respondents. The control of the data was through triangulation of three axes, namely the theories of prison space and identity, the legislation governing the prison and rehabilitation and the perception of those involved with the phenomenon. It was concluded that there is a predisposition of respondents sample to share and reinforce the idea of the impossibility of rehabilitation, thus compromising their possible outcomes. And to think strategies aimed at developing adequate public policies for those involved in the process reformulate its representations about the condition of arrested and resocialization.